Fetal Anomalies and Labor Complications [36K]. (May 2017) - McCormick, Anna; Simpson, Pippa; Pan, Amy; McIntosh, Jennifer; Hibbard, Judith
Abstract : INTRODUCTION: The purpose of this study was to evaluate labor complications and obstetric outcomes in patients diagnosed with fetal anomalies. METHODS: Using the Safe Labor Consortium, a retrospective dataset including labor information from 19 United States hospitals collected from 2002-2008, we compared patients diagnosed with a viable infant with a fetal anomaly to low risk singleton pregnancies. The primary outcome was need for operative vaginal delivery or cesarean delivery. Secondary outcomes include: maternal outcomes–bleeding (administration of blood products, abruption, postpartum hemorrhage, uterine rupture, hysterectomy), malpresentation, maternal ICU admission or death, chorioamnionitis/endometritis, lacerations (third- or fourth-degree), shoulder dystocia and birth injury. Chi-Square or Fisher's exact test was used to examine the association between anomaly and secondary outcomes. Odds ratios and confidence intervals were calculated. RESULTS: We evaluated 5360 patients with a fetal anomalies and compared them to 93, 129 patients with low risk singleton pregnancies. There was no significant difference in need for operative vaginal delivery between groups (OR 0.98 95% CI 0.88, 1.10). There was a significant increase risk of cesarean delivery in the patients with anomalies (OR 1.5 95% CI 1.39, 1.62), as well as incidence of malpresentation (OR 1.27 CI 1.11, 1.45) and breech presentation (OR 1.7 CI 1.41, 2.18), intrapartum fetal distress (OR 1.30 CI 1.15, 1.48) and birth injury (OR 1.88 CI 1.53, 2.30). CONCLUSION: Patients diagnosed with a fetal anomaly are at increased risk of cesarean delivery, malpresentation and birth injury. These increased risks should be taken into consideration in management of these patients.